IMPACT OF ANTECEDENTS OF TAX ADMINISTRATION MODERNIZATION AND AWARENESS ON INDIVIDUAL TAXPAYER’S COMPLIANCE IN JAKARTA - INDONESIA - Riris Rotua Sitorus (STIE Binaniaga, 2018)
This study provides empirical evidence on the effect of modernization of tax administration and awareness on compliance of individual taxpayers in North Jakarta. The Components of modernization of tax administration that being exogenous variables are e-registration, e-filing, e-payment, e-counseling, e-SPT, and e-invoicing. Awareness taxpayer variable is another exogenous variable. Tax compliance is an endogenous variable in this study. The respondents of this study were 65 individual taxpayers, freelancers and also workers as a tax consultant. Using the Smart PLS software, proved that e-registration, e-filing, e-payment, e-counseling, e-SPT, and einvoicing significantly influenced taxpayer’s compliance. While awareness of the taxpayer does not have any influence on taxpayer’s compliance.Key words: Modernization of tax administration, Awareness, Compliance, Individual taxpayers